G336(P) Electronic observations and early warning scoring in a specialist children's hospital. (27th April 2016) - Tay, C; Sefton, G; Selby, A; Tume, L
Abstract : Aim: To determine the impact of electronic vital sign data recording and paediatric early warning (PEW) scoring, 2 months after the implementation of MEDITECH 6 electronic health records, and to explore how electronic systems are used both by doctors on ward rounds and nurses recording observations. Methods: This was a prospective observational study on a cardiac ward, in a specialist children's hospital. An independent observer undertook 104 h of observations over 4 weeks, shadowing medical ward rounds (WR) and nursing staff undertaking and recording vital sign observations. The method of documentation of vital signs and the length of time taken for documentation were noted. How often doctors reviewed the patients' vital sign observations and PEW score trends during ward rounds were noted. Nurses were asked for their perceptions of recording vital signs on the MEDITECH 6 system compared to the previous paper system. Results: 135 episodes of vital signs recording by nursing staff were observed and 123 vital signs and PEWs score reviews during the morning WR were observed. Two methods were used by nursing staff for recording vital signs. In most cases vital signs were recorded electronically at the patient's bedside, immediately after they were obtained (58.5%, n = 79). A second method used was recording vital sign observations on any available surface and documenting electronically at a later stage (41.5%, n = 56). The available surfaces used included scrap paper, paper towels and discarded packaging. The mean time taken to record and document bedside observations was 3 min 41 s (Figure 1 ). The mean time between recording vital signs on an available surface and documenting was 8min 46 s (the shortest was 30 s and the longest was >1 hr) (Figure 2 ). On the morning WR, vital signs and PEWs trends were looked at when reviewing the patient in three quarters of cases (74.0%), but in 26% of cases they were not. Subjectively, most nurses felt documenting on the electronic system was slower than the original paper system. Conclusions: There were some delays in recording vital signs and thus PEW calculation using the electronic system and doctors did not review observations and PEW score trends for all patients during ward rounds.